“Buy It as-a-Service”: Review of the Sustainable Servitization and Product-Service Systems Literature - Kohtamäki, Marko; Rabetino, Rodrigo; Parida, Vinit; Sjödin, David; Bigdeli, Ali Ziaee; Baines, Tim (Palgrave Macmillan, 2026)
Sustainable product-service systems integrate products, services, and software in ways that potentially enable the creation of environmental, societal, and economic value. The present chapter intends to revisit the product-service systems literature and discuss sustainable servitization as a process, creating an understanding of how to achieve a sustainable business model and enterprise. The study identifies three clusters of research for future sustainable servitization research to consider: (1) sustainable PSS integration across industries: eco-efficiency, design, industrialization, and innovation practices; (2) digital servitization for cleaner and smarter production in circular value systems; (3) implementing circular economy principles through PSS-enabled business model innovation and green servitization. Sustainable servitization research is expanding rapidly, highlighting the role of the interplay between sustainability and digitalization over the product life cycle, moving from product-oriented perspectives toward use-oriented and outcome-oriented perspectives.
Keywords: Product-Service systems, Servitization, SPSS, PSS; Service design; Digital servitization; Dynamic capability theory; Manufacturing companies; Sustainable life cycle product-service; fi=Strateginen johtaminen|en=Strategic Management|